Post-Translational Modifications of Deubiquitinating Enzymes: Expanding the Ubiquitin Code - Wang, Yanfeng; Wang, Feng (Frontiers in Pharmacology, 2021)
Ubiquitination is an important post-translational modification (PTMs) in eukaryotes involved in many biological events. This process could be reversed by deubiquitinating enzymes (DUBs), by which conjugated ubiquitin (Ub) molecules can be removed from targeted substrates. Indeed, owing to their role as essential enzymes in regulating all ubiquitin-related processes, the abundance, localization, and catalytic activity of various DUBs are tightly regulated to ensure their exact response. Dysregulation of DUBs can have dramatic physiological consequences and cause a variety of physiological disorders and diseases, such as cancer, neurodegeneration, and inflammatory diseases. Some principles, such as transcription and translation, or accessory domains and binding proteins, or inhibitors, have been implicated in many aspects of DUBs regulation. Beyond this layer, emerging studies show that DUBs functions can be regulated by a variety of post-translational modifications, which affect the abundance, localization, and catalytic activity of DUBs significantly. The most extensively studied post translational modifications are phosphorylation, which has been reported in various DUBs. Besides phosphorylation, some DUBs are known to be ubiquitinated, SUMOylated, acetylated, oxidated and hydroxylated. In this review we summarize the current knowledge of post translational regulation of DUBs.